2019
DOI: 10.1021/acssuschemeng.9b02405
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Coffee Waste-Derived Porous Carbons as Anode Materials for High-Performance Sustainable Microbial Fuel Cells

Abstract: Microbial fuel cell (MFC) is a sustainable technology that can produce electrons using microbes. However, low power density and high cost are the two major issues that hamper the development of MFCs. In this study, we demonstrated that renewable coffee waste-derived activated carbons (CWACs) can serve as anode materials in Escherichia coli system-based MFCs. By modifying the CWAC pore size, we achieved a power density of 3927 mW m–2, which was higher than that of commercial activated carbon (975 mW m–2). The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…The Nyquist-EIS design was studied in the 100 kHz to 100 mHz frequency range with 1.00 mV AC amplitude. It reduced the biofilm disturbance during EIS analysis and stopped the biofilm detachment effect [ 54 ]. Figure 9 shows the observed Nyquist-EIS plot for the GO and GO-PANI anodes, which were affected by kinetic reaction and diffusion with solution resistance (R s ) and charge-transfer resistance (R ct ).…”
Section: Resultsmentioning
confidence: 99%
“…The Nyquist-EIS design was studied in the 100 kHz to 100 mHz frequency range with 1.00 mV AC amplitude. It reduced the biofilm disturbance during EIS analysis and stopped the biofilm detachment effect [ 54 ]. Figure 9 shows the observed Nyquist-EIS plot for the GO and GO-PANI anodes, which were affected by kinetic reaction and diffusion with solution resistance (R s ) and charge-transfer resistance (R ct ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, it is an eco-friendly method, no harmful gases are generated during preparation, the product has an organized structure, and a larger amount of product is provided. Recently, Hung et al [48] used a renewable waste coffee-based anode to enhance the power density in MFCs. The authors converted waste materials into valuable carbonized materials and applied them as an anode in an MFC by reducing waste from the environment.…”
Section: Natural Biomass Materials For the Anodementioning
confidence: 99%
“…The results showed power densities in case of SMFC and DMFC i.e., 872.7 mW/m 2 and 1468.85 mW/m 2 . Recently, Hung et al [155] studied coffee waste-derived carbon anode and obtained the 3927 mW/m 2 power density. This study demonstrated that the high quality of an electrode can increase the energy generation to meet the energy requirement via MFC approach.…”
Section: Mechanism Of Electricity Generation and Pollutant Removal In Mfcsmentioning
confidence: 99%